The Realization of Individual Instances in a Multilingual Generation System - Everaert, Guy; van Steenberghe, Thierry (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1994)
AbstractThis paper presents multilingual sentence generation in the GENESE project, part of the efforts to develop pivot-language based machine translation. The handling of individual instances will be developed and the problem of mass expressions will be highlighted. This will illustrate the use of available linguistic theories for the generation of individual instances in GENESE.